Оценивание и визуализация степени робастности проектируемых сар простыми программными средствами пакета Матлаб - Осичев, Александр Васильевич; Богаевский, Александр Борисович (НТУ "ХПИ", 2013)
In materials of paper the simple approach proposed and with examples are shown as to obtain robustness degree estimaftion and visualization to designed control system by simple software means of Matlab.
Robustness degree estimaftion and visualization to designed control system with simple software means of Matlab
Keywords: электромеханическая система; модальный регулятор; синтез САР; структурная схема САР; алгоритм оценивания синтезированной САР